The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1042/bst0360300
|View full text |Cite
|
Sign up to set email alerts
|

Why expression of some genes is disallowed in β-cells

Abstract: A differentiated beta-cell results not only from cell-specific gene expression, but also from cell-selective repression of certain housekeeping genes. Indeed, to prevent insulin toxicity, beta-cells should handle insulin stores carefully, preventing exocytosis under conditions when circulating insulin is unwanted. Some ubiquitously expressed proteins would significantly jeopardize this safeguard, when allowed to function in beta-cells. This is illustrated by two studied examples. First, low-K(m) hexokinases ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 36 publications
(54 reference statements)
4
79
0
Order By: Relevance
“…Our results therefore confirm previous studies in which protein expression and activity of GPD2 have been shown to be similar in primary sorted β-cells and the INS-1 cell line, being about 10-fold higher in these cells compared with islet non-β-cells [54]. Furthermore, expression of Gpd2 has previously been studied in conjunction with the β-cell 'disallowed' gene Ldh [58]; the ratio of Gpd2-to-Ldh was found to be two to three orders of magnitude greater in primary β-cells and INS-1 cells than in other islet cells [54]. Moreover, impairments in the glycerol phosphate shuttle have been observed in animal models of T2D [59,60] and in T-lymphocytes from T2D patients [61].…”
Section: Figure 8 Gsis From Mouse Islets Is Unaffected By Phs Whereasupporting
confidence: 91%
“…Our results therefore confirm previous studies in which protein expression and activity of GPD2 have been shown to be similar in primary sorted β-cells and the INS-1 cell line, being about 10-fold higher in these cells compared with islet non-β-cells [54]. Furthermore, expression of Gpd2 has previously been studied in conjunction with the β-cell 'disallowed' gene Ldh [58]; the ratio of Gpd2-to-Ldh was found to be two to three orders of magnitude greater in primary β-cells and INS-1 cells than in other islet cells [54]. Moreover, impairments in the glycerol phosphate shuttle have been observed in animal models of T2D [59,60] and in T-lymphocytes from T2D patients [61].…”
Section: Figure 8 Gsis From Mouse Islets Is Unaffected By Phs Whereasupporting
confidence: 91%
“…When examining these figures, it should be born in mind that the overall islet mRNA profile reflects the mean of phenomena in different cell types. Thus, although most changes are likely to have occurred in beta cells (∼70-80% of islet mass), some may have occurred in non-beta cells, especially for genes normally disallowed in beta cells like the lactate/pyruvate transporter Mct1 (also known as Slc16a1) [1,38]. Please also note that changes in mRNA levels may result from altered transcription or mRNA stability and that the higher level of complexity due to alternative mRNA splicing was not addressed.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of pancreatic beta cells to secrete insulin in response to nutrient stimulation depends on adequate expression of genes important for glycolysis, mitochondrial metabolism and insulin biosynthesis, such as preproinsulin, Glut2 (also known as Slc2a2) and glucokinase, and on the repression of genes potentially deleterious to beta cell function [1], including hexokinase 1 and lactate dehydrogenase A [2]. Besides acutely regulating insulin biosynthesis and secretion, subacute and prolonged changes in nutrient availability exert pleiotropic effects on the beta cell phenotype, such as altered function, survival, growth and differentiation [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…One of the deeply repressed genes in islets of Langerhans is Mct1, encoding the monocarboxylate transporter MCT1, which mediates the transport of lactate and pyruvate across cell membranes and is present in all tissues except adult beta-cells (Otonkoski et al 2007;Quintens et al 2008). Inadvertent expression of MCT1 in beta-cells results in hypoglycemia after physical exercise due to inappropriate insulin release (Otonkoski et al 2003).…”
Section: Disallowance In Islets Of Langerhansmentioning
confidence: 99%
“…Two studies previously reported on disallowance in islets (Quintens et al 2008;Pullen et al 2010), but this study is the first to analyze the phenomenon in a broad set of tissues and provide mechanistic insights. In summary, we propose that tissue-specific disallowance of housekeeping genes is required for the specialized function of differentiated tissues.…”
Section: Disallowed Genesmentioning
confidence: 99%